2016
DOI: 10.1021/acs.joc.6b01568
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Octahydroindoles via a Domino Robinson Annulation/5-Endo Intramolecular Aza-Michael Reaction

Abstract: A straightforward, two-step asymmetric synthesis of octahydroindoles has been developed on the basis of two complementary strategies: (i) an organocatalyzed Michael reaction followed by a tandem Robinson−aza-Michael double cyclization catalyzed by PS-BEMP, and (ii) a diastereoselective cyclization, which formally constitutes a remote 1,6 asymmetric induction mediated by PS-BEMP. This allowed the construction of complex octahydroindoles with up to four stereocenters, excellent enantioselectivities (up to 95% ee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Claudio Parra and co‐authors [83] reported an asymmetric, organocatalyzed, single‐pot Michael addition between acyclic β‐keto ester 212 and 213 followed by a tandem Robinson‐aza‐Michael cyclization catalyzed by XII in presence of Lithium acetate and mediated by PS‐BEMP, that affords polyfunctionalized octahydroindoles 214 bearing four stereocenters, with extraordinary enantioselectivities (up to 95 % ee) and high diastereoselectivities [Scheme 53]. They had also carried out DFT calculations to investigate the reason behind the complete diastereoselectivity exercised by the benzyl substituent on the bicycle formation.…”
Section: Organocatalytic Enantioselective Michael Addition Reactionsmentioning
confidence: 99%
“…Claudio Parra and co‐authors [83] reported an asymmetric, organocatalyzed, single‐pot Michael addition between acyclic β‐keto ester 212 and 213 followed by a tandem Robinson‐aza‐Michael cyclization catalyzed by XII in presence of Lithium acetate and mediated by PS‐BEMP, that affords polyfunctionalized octahydroindoles 214 bearing four stereocenters, with extraordinary enantioselectivities (up to 95 % ee) and high diastereoselectivities [Scheme 53]. They had also carried out DFT calculations to investigate the reason behind the complete diastereoselectivity exercised by the benzyl substituent on the bicycle formation.…”
Section: Organocatalytic Enantioselective Michael Addition Reactionsmentioning
confidence: 99%
“…However, brief descriptions of the examples reported to date, including the main author, year of publication and type of catalyst employed are specified in Table 1. Strategies involving Mannich/IMAMR, [47][48][49][50][51][52][53][54][55][56][57][58][59] α-aminoxylation/ IMAMR, [60][61][62][63][64] aza-Friedel-Crafts/IMAMR, [65] cross metathesis/ IMAMR, , [18,28] aza-Morita-Baylis-Hillman/IMAMR, [66] Robinson annulation/IMAMR, [67][68][69][70][71] oxa-Mannich/IMAMR, [72] aza-Henry/IMAMR, [73] peptide coupling/IMAMR, [38] aza-Rahuhut-Currier/IMAMR, [74] Betti/IMAMR, [75] enamine formation/IMAMR [76] and carbene insertion/IMAMR [77] are collected in this table.…”
Section: Tandem Reactions Non-initiated By An Imamrmentioning
confidence: 99%
“…A piperidinone synthesis that may involve a Mannich-Michael sequence An exo-activated endo-aza-Michael is a component of a rather complex tandem process leading to octahydroindoles 100 and 101 (Scheme 25). 50 The sequence involves a Michael addition of a -ketoester, 99, to an unsaturated aldehdye, followed by an intramolecular Aldol process. This generates an intermediate 102 which then undergoes an exo-activated endo-aza-Michael addition.…”
Section: The Hidden Endo-aza-michaelmentioning
confidence: 99%